Governance models of training for employment: a European perspective - Greinert, Wolf-Dietrich [Verfasser] (My University, 2010)
"Internationally, the question of how to qualify the workforce seems to be of increasing importance for competitive economies. How can politics govern the quantity and quality of employment structures and optimise both? In this article a theoretical framework is outlined that has been developed for the analysis of institutional constructs serving workforce qualification. Its most important elements and mechanisms are explained in a model and a typology - both based on a European/German perspective." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; I 2.2 Europa; EU-Bildungspolitik; Berufsbildungspolitik; Beschäftigungsfähigkeit; Bildungssteuerung; Europa